Debt portfolios - Thomas Hintermaier; Winfried Koeniger (Queen Mary University of London, Department of Economics, 2009)
We provide a model with endogenous portfolios of secured and unsecured household debt. Secured debt is collateralized by durables whereas unsecured debt can be discharged in bankruptcy procedures. We show that the model matches the main quantitative characteristics of observed wealth and debt portfolios in the US and some of the observed changes over time. Furthermore, we establish two quantitative results. Firstly, modest levels of risk aversion are necessary to match observed debt portfolios. Secondly, durables do not improve consumers' access to unsecured credit, and plausible variations of durable exemptions in bankruptcy procedures have very small effects on the equilibrium.
Keywords: E21; D91; 330; household debt portfolios; durables; collateral; income risk; bankruptcy; Private Verschuldung; Konkurs; Kreditsicherung; Dauerhaftes Konsumgut; Einkommen; Risiko; USA